Hallux Arthrodesis - Vilá y Rico, Jesús; Hernanz, Yolanda; Abarquero-Diezhandino, Ana (Journal of the Foot & Ankle, 2022)
Hallux arthrodesis is a prominent technique, both in primary surgery and in reoperations. New devices and instruments have significantly improved outcomes, minimizing complications, although it is a demanding intervention from the technical point of viewand not exempt from complications. Arthrodesis is indicated in cases of primary or secondary hallux rigidus, and also as a salvage surgery for previous failed treatments such as joint sparing osteotomies or arthroplasty. Proper arthrodesis positioning is important, maintaining a dorsiflexion of 10-15º with a hallux valgus angle of nearly 10º and neutral rotation, in order to prevent complications such as hallux varus or interphalangeal joint arthritis. Arthrodesis outcomes are excellent from the clinical-functional and radiological point of view, with a union rate of 93.5%; however, this technique is not exempt from complications such as nonunion, malunion, need for hardware removal, and skin and healing problems. Nonetheless, this technique provides excellent outcomes. Level of Evidence V; Therapeutic Studies; Expert Opinion.